2019
DOI: 10.20533/ijels.2046.4568.2019.0073
|View full text |Cite
|
Sign up to set email alerts
|

Learning Management Systems and Student Performance

Abstract: In today's technology driven societies, academic institutions, especially at the tertiary level, are incorporating Information and Communication Technologies (ICTs), utilizing learning management systems (LMS) and adopting blended learning approaches to improve student performance and enhance student learning. Currently a good deal of research is conducted to assess the effectiveness of such techniques and technologies on student learning and performance. A great deal of this research deals with LMS's, e-learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 23 publications
(10 reference statements)
2
20
0
Order By: Relevance
“…In today's technology-driven societies, higher education institutions, especially at the tertiary level, are adopting blended learning approaches to enhance student learning and improve student performance [1]. The blended learning model combines traditional classroom teaching and an e-learning system [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In today's technology-driven societies, higher education institutions, especially at the tertiary level, are adopting blended learning approaches to enhance student learning and improve student performance [1]. The blended learning model combines traditional classroom teaching and an e-learning system [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the study found that while the mean effect size for the purely online versus face-to-face contrasts was not significantly different from 0 (g+ = +0.05, p = .46), the mean effect size of the blended versus face-toface contrasts was significantly different from zero (g+ = +0.35, p < .0001) [19]. Many researchers concluded that the reported effects of blended learning on students' achievement were inconsistent and mixed [1][2], [9], [12], [14], [20].…”
mentioning
confidence: 99%
See 3 more Smart Citations